INTEGRALITY IN CARE: FROM PRIMARY HEALTH CARE TO SPECIALTY - da Silva Nogueira, Raquel (Health and Society, 2023)
Introduction: The right to health, access and integrality of care are the doctrinal rights of the SUS, guarantee these rights to the user within the Network of Health Care, starting from the one that is the care provider, Primary Health Care, Secondary Care in the field of specialty, has been shown over the years as a great challenge. Objective: To identify pertinent questions, in the different bibliographic findings, that relate the difficulties of users’ access to health care levels. Method: This is a literature review of the literature. Results: A total of 10 articles were found. We recognize that no organization brings together all the resources and skills necessary to solve the health problems of a population in its various life cycles. We see that it is opportune to share some experiences reported in literatures on the integration of services, which we think seem interesting to researchers and managers. Final considerations: We consider that the integration between different points of attention, the insufficiency of formal flows between health care levels and the disarticulation of policies that regulate secondary care are obstacles to the guarantee of integral care, making the care process incomplete and fragmented on the network. Integrality in Care, Integrality and Basic Attention, Ambulatory Specialized Attention, Secondary Care.